(untitled) (Journal of Hama University, 2025)
The research aims to identify the level of emotional creativity among a sample of fourth-year students in the department of psychological counseling at Tishreen university. It also aims to identify the differences in the level of emotional creativity of according to the variables (university average and scientific specialization). The research sample included (64) fourth- year students in the department of psychological counseling at Tishreen university The researcher used the Emotional Questionnaire(Al-Bilal,2020), after studding its psychometric properties. The results of the research showed that the level of emotional creativity among the research sample of fourth-year students in the department of psychological counseling at Tishreen university was average, The results also showed that there were no statistically significant differences in the level of their emotional creativity depending on the scientific specialization variable (scientific and literary), While differences were found according to the university average variable in favor of students whose averages were good and very good. Based on these results, the researcher presented several proposals, the most important of which is interest in developing emotional creativity among psychological counseling students and preparing university lectures and seminars on the importance of emotional creativity in comforting situations and solving problems effectively.